Application of Propensity Score Matching for Analyzing Factors Contributing to Pre-Diabetes - Oktaviani Aisyah Putri; Anwar Fitrianto; Aam Alamudi (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2025)
Inappropriate comparisons between control and treatment groups can be caused by overlapping factors, usually called confounders. Propensity score methods help reduce bias from measured confounding by summarizing the distribution of multiple measured confounders into a single score, based on the probability of receiving treatment. This study applies binary logistic regression to estimate propensity scores and identify risk factors that significantly influence complications in fasting blood glucose levels. Nearest Neighbor Matching (NNM) is used with various caliper and score orders to determine the most effective combination in reducing bias. The results show that gender becomes a confounding variable. Both the order of propensity scores and caliper selection affect the outcome of the matching process. Matching with a random order and caliper yields the best result, with 99,93 percent reduction bias. The significance of the average treatment effect for treated (ATT), all condition order with caliper indicates that gender have a positive relationship and significantly affects fasting blood glucose levels. Also, based on the matching results with the best combination, it indicates that age, academic position, structural position, education level, and lecturer performance do not influence abnormal fasting blood sugar (FBS).